PENERAPAN METODE ARAS (ADDITIVE RATIO ASSESSMENT) DALAM MENENTUKAN LOKASI PERUMAHAN TERBAIK (STUDI KASUS CV. ANUGRAH PROPERTY) - Supiyan, Dede; Rhamdhan, Ridzal (Pogram Studi Sistem Komputer Universitas Serang Raya, 2025)
This research aims to apply the ARAS (Additive Ratio Assessment) method in determining the best housing location for CV. Anugrah Property. Optimal housing location is critical to the success of a property project. The ARAS method is a ranking-based location selection method that allows decisions to be made by considering a number of relevant criteria. This case study was carried out by identifying key criteria that influence the success of housing locations, including accessibility, infrastructure availability, economic growth potential, and consumer preferences. Then, the relative weight of each criterion is determined through consultation with property industry experts and CV owners. Anugrah Property. Next, data regarding these criteria are collected and evaluated for each location considered. The ARAS method is used to calculate data scores from each location and allows ranking of locations based on predetermined criteria. The results of this analysis make it easier to determine the best location for a CV housing project. Anugrah Property. The results of this research can provide strong guidance for CV. Anugrah Property in choosing the most profitable housing location and in accordance with their business goals.